2016
DOI: 10.1152/ajpregu.00415.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen replacement on stress-induced cardiovascular responses via renin-angiotensin system in ovariectomized rats

Abstract: The purpose of this study was to determine whether chronic estrogen replacement in ovariectomized rats inhibits the pressor response to psychological stress by attenuating the activation of the renin-angiotensin system. Female Wistar rats aged 9 wk were ovariectomized. After 4 wk, the rats were randomly assigned to be implanted subcutaneously with pellets containing either 17β-estradiol (E2) or placebo (Pla). After 4 wk of treatment, the rats underwent cage-switch stress and, in a separate experiment, a subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…Freely moving rats aged 16 weeks in separate sets of Pla (n = 9) and E2 groups (n = 8) were catheterized with venous cannula, as previously described [34]. Blood sampling was performed on the 5th-day post-cannulation.…”
Section: Assessment Of Plasma Acyl Ghrelin Levelmentioning
confidence: 99%
“…Freely moving rats aged 16 weeks in separate sets of Pla (n = 9) and E2 groups (n = 8) were catheterized with venous cannula, as previously described [34]. Blood sampling was performed on the 5th-day post-cannulation.…”
Section: Assessment Of Plasma Acyl Ghrelin Levelmentioning
confidence: 99%
“…The rats were implanted with telemetry devices (Data Sciences International, MN, United States) through the abdominal aorta as described previously ( Tazumi et al, 2016 ). Simply, the rats were placed on a heated surgical field in dorsal recumbency under anesthesia with isoflurane (2.5–3.5%).…”
Section: Methodsmentioning
confidence: 99%
“…In the previous few decades, several reports have shown protective effects of hormone replacement therapy in menopausal women against ischemic heart disease, coronary heart disease, [ 73 , 74 , 75 ]. E2 replacement has also shown effective protection against psychological stress seen in estrogen-replaced ovariectomized rats, and different ERs have also been proven to confer cardio-protection [ 35 , 76 , 77 ]. Hale et al reported that estrogen replacement reduces both myocardial infarct size and ventricular arrhythmias induced by ischemia/reperfusion in both female and male rabbits [ 78 ].…”
Section: Discussionmentioning
confidence: 99%